FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI NANOSPRAY GEL EKSTRAK ETANOL RIMPANG RUMPUT TEKI (Cyperus rotundus) TERHADAP Staphylococcus epidermidis DAN Cutibacterium acnes - Nurista Dida Ayuningtyas; Riskianto; Eugenia Nayumi Gozal (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Acne is a common inflammatory skin condition among teens and adults. Topical treatment with chemical agents often carries the risk of irritation and photosensitization. This has led to the exploration of natural alternatives such as Nutgrass (Cyperus rotundus L.), which possesses antibacterial activity. The objective of this study was to formulate a nanospray gel as a topical delivery system and to test the antibacterial activity of the formulation against S. epidermidis and C. acnes. Cyperus rotundus was extracted via maceration using 96% ethanol; antibacterial activity tests were conducted on both the extract and the formulation. The nanospray gel formulation was prepared with varying extract concentrations: F1 (1%), F2 (2%), and F3 (3%). Subsequently, transmittance tests, physical characterization, and antibacterial activity assessments were performed using the disk diffusion method. The inhibition percentages of the extracts against S. epidermidis and C. acnes at a 35% concentration were 86.14% and 92.11%, respectively. The transmittance test results for the formulations were 94.1%, 53%, and 56%, respectively. Particle size testing of F1 yielded 158.06 ± 4.60 nm with a zeta potential of -40.46 ± 2.1 mV. The antibacterial activity test results for C. acnes in formulations F1–F3 were 1.63 mm, 2.3 mm, and 2.23 mm, respectively. The characteristics of the nanospray formulations met quality standards; however, the antibacterial activity was still weak, necessitating optimization of the extraction process.